Penerapan Pembelajaran Berbasis Masalah (Problem Based Learning ) Untuk Meningkatkan Prestasi dan Kemandirian Belajar Siswa Pada Mata Pelajaran PKWU Di Kelas XII IPS2 Semester 1 Tahun Pelajaran 2019/ 2020 - Budi, Sihono Setyo (Universitas Alma Ata, 2020)
This research in aimed to find out if Problem Based Learning Model can improve the independence of learning and learning achievment at class XII IPS2 in MAN 1 Kulon Progo. The subject of this reasearch the students of MAN 1 Kulon Progo at class XII IPS2 for 33 students. The datum are obtained by using observation sheet and quantitative and qualitative data analysis. It is shown that the are significant improvemens on cycle I, cycle II , and cycle III. The everage scores of learning achievement are 65,7 on cycle I, 71,6 on cycle II and 73,5 on cycle III. The evarega score of independence of learning are 73,06, on cycle I, 76,51 on cycle II and 88,18 on cycle III. Keywords : Problem Based Learning Model, Learning Achievement, independence of learning,